Application of Internal Factory Production Quality Control of Steel Products According to HRN EN 1090 Standard (Proceedings of Faculty of Civil Engineering, 2019)
The quality of steel products and quality assurance procedures in the Republic of Croatia are legally regulated and standardized. Since Croatia is a full member of the European Union, it is obligatory to apply the EU Regulation no. 305/2011 of the European Parliament and of the Council and the application of the standards group HRN EN 1090. The scope of the factory production control process of producing steel elements requires the appropriate qualified personnel in order to implement the factory quality control system. The paper presents a brief overview of the HRN EN 1090 standards group, their classification and application in a single technological process. Through the example of the steel construction of the future commercial building, the procedure of performing quality control according to HRN EN 1090-2 for the EXC2 performance class is shown. The manufacturing process of the steel structure during factory production control is divided and analyzed in several key phases: basic material control, welding documentation overview, dimension inspection, visual inspection, anti-corrosion protection and CE marking or declaration of properties. All the processes and procedures that take place within the factory are equally important to achieve the final goal, that is, a quality steel element according to standard HRN EN 1090 for the future building construction. The aim of this paper is to point out the importance of carrying out the factory quality control, which significantly reduces the possibility of failures, both during the production of steel elements as well as during its use in the case of the construction breakdown.
Keywords: quality control; production processes; HRN EN 1090; production of steel elements